Soybean Salt Tolerance 1 (GmST1) Reduces ROS Production, Enhances ABA Sensitivity, and Abiotic Stress Tolerance in Arabidopsis thaliana - Ren, Shuxin; Lyle, Chimera; Jiang, Guo-liang; Penumala, Abhishek (Frontiers in Plant Science, 2016)
Abiotic stresses, including high soil salinity, significantly reduce crop production worldwide. Salt tolerance in plants is a complex trait and is regulated by multiple mechanisms. Understanding the mechanisms and dissecting the components on their regulatory pathways will provide new insights, leading to novel strategies for the improvement of salt tolerance in agricultural and economic crops of importance. Here we report that soybean salt tolerance 1, named GmST1, exhibited strong tolerance to salt stress in the Arabidopsis transgenic lines. The GmST1-overexpressed Arabidopsis also increased sensitivity to ABA and decreased production of reactive oxygen species (ROS) under salt stress. In addition, GmST1 significantly improved drought tolerance in Arabidopsis transgenic lines. GmST1 belongs to a 3-prime part of Glyma.03g171600 gene in the current version of soybean genome sequence annotation. However, comparative RT-PCR analysis around Glyma.03g171600 genomic region confirmed that GmST1 might serve as an intact gene in soybean leaf tissues. Unlike Glyma.03g171600 which was not expressed in leaves, GmST1 was strongly induced by salt treatment in the leaf tissues. By promoter analysis, a TATA box was detected to be positioned close to GmST1 start codon and a putative ABRE and a DRE cis-acting elements were identified at about 1kb upstream of GmST1 gene. The data also indicated that GmST1-transgenic lines survived under drought stress and showed a significantly lower water loss than non-transgenic lines. In summary, our results suggest that overexpression of GmST1 significantly improves Arabidopsis tolerance to both salt and drought stresses and the gene may be a potential candidate for genetic engineering of salt- and drought-tolerant crops.